Optimalisasi Perencanaan Proyek Konstruksi melalui Pendampingan Penyusunan Studi Kelayakan Bisnis di PT Sahabat Anugerah Sejati - Ryo Setyadi; Fitriasuri Fitriasuri; Bakti Setyadi; Septiani Fransisca; Poppy Indriani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service program aims to optimize construction project planning through assistance in preparing a business feasibility study at PT Sahabat Anugrah Sejati. The construction sector is a strategic industry that requires effective resource management, proper risk mitigation, and accurate planning to ensure project success. Therefore, the program supported the partner in analyzing financial, managerial, market, and economic aspects prior to making investment decisions for the proposed project. The results show that the project is feasible based on the Net Present Value (NPV) and Internal Rate of Return (IRR) analyses. An efficient organizational structure, a competent management team, and strong supervision mechanisms further strengthen the project’s operational readiness. Increasing demand for construction services also enhances the company’s market prospects. However, several areas still require improvement, including heavy equipment utilization, material efficiency, and digital marketing strategies. This program provides strategic recommendations to help PT Sahabat Anugrah Sejati improve project feasibility, operational effectiveness, and long-term business sustainability.